- 1-800-665-6601
- [email protected]

Given is an equation f(x) = 2 x + 3.

To find the inverse y =2 x + 3 Switch ‘x’ and ’y’ places x = 2y + 3

Solve for ‘y’ Subtracting 3 on both sides of the equation x - 3 = 2 y

Now divide both sides by 2.

This gives, (x - 3)/2 = 2 y/2

Therefore f(x)

Given is an equation f(x) = 5 x + 6.

To find the inverse y =5 x + 6 Switch ‘x’ and ’y’ places x = 5y + 6

Solve for y Subtracting 6 on both sides of the equation x - 6 = 5 y

Now divide both sides by 5.

This gives, (x - 6)/5 = 5 y/5

Therefore f(x)